Applying societal metabolism to characterize water availability, requirement, and scarcity in agriculture. A case study of Mexico - Escamilla, Enrique Zunzunegui; Ordoñez, Gonzalo Ángeles; Orozco-Ramírez, Quetzalcóatl; Caballero Castrillo, Maribel A.; Morales Mora, Miguel A. (Frontiers in Sustainable Food Systems, 2023)
Given the environmental challenges of soil depletion, water scarcity, and resource competition, the agricultural products market demands a continuous increase in annual crop productivity. Nevertheless, it is often overlooked whether there are favorable conditions within the biophysical constraints of the natural system to meet such a requirement. This paper contemplates an integrated analysis that connects the interaction of water-land-food and production value (WLFPV) from the availability, requirement, and scarcity of water based on the Multi-Scale Integrated Analysis of Societal and Ecosystem Metabolism (MuSIASEM) framework. This study evaluates nine crops (agave, avocado, berries, coffee, figs, native maize, pitaya-pitahaya, critical banana, and vanilla) of high commercial value from the central-eastern region of Mexico to obtain their metabolic profiles and answer this question. For this, relative water stress index (RWSI) was used as well as intensity and metabolic density indicators for each crop. The findings were then visualized and communicated through maps. The results indicate that: (1) The annual available water satisfies the total water requirement of the crops of 1,782.6 hm3, planted in 276,965 hectares that produce 803,191 tons of food with a value of 165.2 million USD. (2) 65% of the area dedicated to the production of agave, pitaya-pitahaya, and other crops is affected by a water deficit. This area’s relative water stress index (RWSI) ranges from moderate to high. In the short term, they can constrain agricultural development areas. (3) The metabolic intensity and density indicators show that the combined efficiency of the water demand/supply relationship for native maize was very deficient in 23 of the 50 municipalities. From our analysis perspective, it was possible to understand the changes occurring in the Socio-Ecological System of the nine agricultural chains. A trend in decreased rainfall and water levels in the aquifers for food production was observed.